Un nuevo perfil de egreso en la Escuela de Medicina: cuál es el sentido - Alarcón R., Gisela (Revista Hospital Clínico Universidad de Chile, 2014)
The competency-based curriculum has as a reference point the desired profile defined by the University of Chile School of Medicine for its graduates. It is therefore necessary for all teachers in this school to know the new profile of graduates as well as the new curricular grid that emerges from it. This article is an attempt to reinforce this need.